CULTURE, POVERTY, AND RELIGION AT A CROSSROADS: CAUSES AND IMPLICATIONS OF CHILD MARRIAGE IN THE SLUMS OF KARACHI - Khatoon, Syeda Uzma; Aleemi, Abdur Rahman (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
Child marriage continues to be prevalent in South Asia, including Pakistan, despite national laws and international agreements prohibiting it. This article aims to discover the causes of child marriage and its implications for child brides. We identify gaps in the implementation of laws, good practices, and program designs, and we propose necessary initiatives. Utilizing a cross-sectional design, a mix of quantitative and qualitative information was obtained from focus group discussions and from a survey of 131 early married females. We found that the cause of child marriage in Pakistan is not simply poverty: it is also deeply rooted in social customs, cultural norms, and traditional and religious beliefs. The psychological, economic, social, and physical consequences of child marriage can be excruciating for these girls, whose education may be curtailed and who are likelier than their unmarried peers to experience emotional, sexual, and physical violence. This study identifies parental decision-making, societal pressures, and entrenched gender roles as key drivers of child marriage. A lack of awareness about the legal marriage age and limited access to education further exacerbate the problem. Our recommendations include standardizing the legal marriage age at 18 years, implementing mass birth registration campaigns, and ensuring access to education for girls. Community-based awareness programs should challenge cultural norms and promote the benefits of delayed marriage. Strengthening laws and empowering local authorities to enforce them are also essential. Moreover, comprehensive poverty reduction programs, vocational training for women, and education reforms are needed if the root causes of child marriage and its often devastating consequences are to be successfully addressed.